Structural and mechanical feasibility study of a variable camber wing (VCW) for a transport aircraft - Macci, S. H. M. (Cranfield University, 1992)
Aerodynamic investigations have shown' that variable camber wings (VCW) for transport aircraft have considerable potential in terms of improving aircraft performance and enhancing their operational flexibility. In order to justify these benefits it is essential that the camber varying system is structurally and mechanically feasible. This research examined the feasibility of providing variable camber to two supercritical aerofoil sections of different'characteristics. The unique method of camber vaTiation was applied by rotating the forward and aft regions of the aerofoil on a circular arc and keeping the surface continuous and matching at their attachment to the main wing box. The change in camber thus increased the chord due to translational motion of the aforementioned regions. The geometries required for varying the forward camber by this method presented formidable design difficulties and no immediate solutions could be found. As a result, an alternative geometry was devised which accepts camber by simply drooping the nose region. A novel idea was developed for aft camber variation, which is considered to be universal for all supercritical aerofoil sections. The system utilises a tracking mechanism which guides a trailing edge element on a continuous arc. Surface continuity is provided by a flexible skin on the upper side and a spring loaded hinged panel on the under side. The flexible skin remains attached to the trailing edge element through a series of roller link arrangement which locate the skin in a separate guide rail. The large moment arm and therefore the increased torsional loads created due to the translational motion of the trailing edge element necessitated investigation of alternative deployment geometries. As a result two additional geometries were schemed. One had reduced radius of rotation and therefore reduced extension, while the other changed camber by drooping the aft region without any chordal extension. Since there was no aerodynamic evidence on the possible benefits offered by these geometries it was decide to postpone them until such information was available. Some detailed aspects of the proposed concept for aft camber variation were considered by applying the system to a modem transport aircraft wing. This resulted in a design which is practically feasible. Justification of this concept was made by designing and testing a half scale structural model of one trailing edge segment. Three dimensional (3-D) geometric investigation showed that the camber-varying elements ride on a frustum of a cone and therefore their deployment is skewed to the line of flight. The 3-D geometric implications of variable camber clearly suggested that the camber variation by rotation on a circular arc, on a tapered wing can be possible if the rotating element is made to flex and twist or it utilises a pin jointed arrangement. To provide the necessary flexibility to the trailing edge element, its structural box best be made from fibre reinforced plastic material. The deployment of the trailing edge element on the structural m(; del was made possible by designing it in laminated wood. Comparison of the proposed variable camber system with a conventional single slotted flap arrangement suggests that the two systems could be equally complex but the variable camber could be slightly heavier., Further systems investigations are required to quantify overall aerodynamic, mass, and cost implications of the use of VCW on transport aircraft.